Case report: Expanding the understanding of the adult polyglucosan body disease continuum: novel presentations, diagnostic pitfalls, and clinical pearls - Gayed, Matthew M.; Sgobbi, Paulo; Pinto, Wladimir Bocca Viera De Rezende; Kishnani, Priya S.; Koch, Rebecca L. (Frontiers in Genetics, 2023)
Introduction: Adult polyglucosan body disease (APBD) has long been regarded as the adult-onset form of glycogen storage disease type IV (GSD IV) and is caused by biallelic pathogenic variants in GBE1. Advances in the understanding of the natural history of APBD published in recent years have led to the use of discrete descriptors (“typical” versus “atypical”) based on adherence to traditional symptomatology and homozygosity for the p.Y329S variant. Although these general descriptors are helpful in summarizing common findings and symptoms in APBD, they are inherently limited and may affect disease recognition in diverse populations. Methods: This case series includes three American patients (cases 1–3) and four Brazilian patients (cases 4–7) diagnosed with APBD. Patient-reported outcome (PRO) measures were employed to evaluate pain, fatigue, and quality of life in cases 1–3. Results: We describe the clinical course and diagnostic odyssey of seven cases of APBD that challenge the utility and efficacy of discrete descriptors. Cases 1–3 are compound heterozygotes that harbor the previously identified deep intronic variant in GBE1 and presented with “typical” APBD phenotypically, despite lacking two copies of the pathogenic p.Y329S variant. Patient-reported outcome measures in these three cases revealed the moderate levels of pain and fatigue as well as an impacted quality of life. Cases 4–7 have unique genotypic profiles and emphasize the growing recognition of presentations of APBD in diverse populations with broad neurological manifestations. Conclusion: Collectively, these cases underscore the understanding of APBD as a spectrum disorder existing on the GSD IV phenotypic continuum. We draw attention to the pitfalls of commonly used genetic testing methods when diagnosing APBD and highlight the utility of patient-reported outcome questionnaires in managing this disease.